Effectiveness and Safety of Botulinum Toxin Type A in Children with Musculoskeletal Conditions: What Is the Current State of Evidence? - Noémi Dahan-Oliel; Bahar Kasaai; Kathleen Montpetit; Reggie Hamdy (International Journal of Pediatrics)
Children with musculoskeletal conditions experience muscle weakness, difficulty walking and limitations in physical activities. Standard treatment includes physiotherapy, casting, and surgery. The use of botulinum toxins appears as a promising treatment on its own, but usually as an adjunct to other treatment modalities and as an alternative to surgery. The objectives were to establish the evidence on the effectiveness, safety and functional outcome of BTX-A in children with musculoskeletal conditions. A literature search using five electronic databases identified 24 studies that met our inclusion criteria. Two randomized clinical trials were included; most studies were case studies with small sample sizes and no control group. Improvements in gait pattern, function, range of motion, reduction of co-contractions, and avoidance of surgical procedures were found following BTX-A injections. Adverse events were not reported in 10 studies, minor adverse events were reported in 13 children and there were no severe adverse events. Additional doses appear safe. BTX-A is a promising treatment adjunct in improving functional outcomes in children with musculoskeletal conditions. Future studies including larger samples, longer follow-up periods and a comparison group are required to provide evidence on the effectiveness and safety of this drug in children with musculoskeletal conditions.